2021
DOI: 10.3390/land10040375
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Tram Networks in the Revitalization of the Warsaw Landscape

Abstract: The current crisis of worldwide agglomeration and economic, spatial, and ownership factors, among others, mean that there is usually a shortage of new green areas, which are socially very beneficial. Therefore, various brownfields or degraded lands along public transport routes, e.g., tram lanes, are effectively transformed for this purpose. The significant potential of tram systems is that they can became a backbone of green corridors across the city. This case study of the Warsaw tram system (total length ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In the same process, greeneries also provide clean air for the urban population and animals [22,51,52]. Therefore, the ecological and environmental development roles of integrating greenery systems in the transport, and built areas is of paramount functions [22,26,58,59,[62][63][64][65][66][67][68][69][70][71][72][73]. We can ably argue that the urban dwellers also enjoy psychological benefits from interacting with urban nature [74][75][76].…”
Section: Integration Between Transport Building and Green Spaces In The Citymentioning
confidence: 99%
See 1 more Smart Citation
“…In the same process, greeneries also provide clean air for the urban population and animals [22,51,52]. Therefore, the ecological and environmental development roles of integrating greenery systems in the transport, and built areas is of paramount functions [22,26,58,59,[62][63][64][65][66][67][68][69][70][71][72][73]. We can ably argue that the urban dwellers also enjoy psychological benefits from interacting with urban nature [74][75][76].…”
Section: Integration Between Transport Building and Green Spaces In The Citymentioning
confidence: 99%
“…Rational protection of cities' existing natural resources and planned, constant development are of key importance here. Maintaining mature trees, introducing various forms of urban greenery, and increasing the biologically active area (especially in the center zone) are the basic conditions for achieving a clean and healthy city [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Greening tram lanes in cities appear to be an important strategy for the development of green corridors as well as enhancing UES [16]. Łukaszkiewicz et al [16] demonstrated how to revitalize the Warsaw cityscape by converting existing tram lines where viable and developing new ones from a "green perspective."…”
mentioning
confidence: 99%
“…Greening tram lanes in cities appear to be an important strategy for the development of green corridors as well as enhancing UES [16]. Łukaszkiewicz et al [16] demonstrated how to revitalize the Warsaw cityscape by converting existing tram lines where viable and developing new ones from a "green perspective." Green tram lanes reduce the noise level during tram operation, improve the aesthetic experience of city streets, and, when skillfullyapplied, allow the sound level from traffic to be reduced by 10.0 to 15.0 dB [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation